Effects of lapatinib on her2-positive and her2-negative canine mammary carcinoma cells cultured in vitro - Leis-Filho, Antonio Fernando [UNESP]; Lainetti, Patrícia de Faria [UNESP]; Kobayashi, Priscila Emiko [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; Laufer-Amorim, Renée [UNESP] (MDPI, 2021)
HER2 is a prognostic and predictive marker widely used in breast cancer. Lapatinib is a tyrosine kinase inhibitor that works by blocking the phosphorylation of the receptor HER2. Its use is related to relatively good results in the treatment of women with HER2+ breast cancer. Thus, this study aimed to verify the effects of lapatinib on four canine primary mammary gland carcinoma cell cultures and two paired metastatic cell cultures. Cultures were treated with lapatinib at concentrations of 100, 500, 1000 and 3000 nM for 24 h and the 50% inhibitory concentration (IC50) for each cell culture was determined. In addition, a transwell assay was performed to assess the ability of lapatinib to inhibit cell migration. Furthermore, we verified HER2 expression by RT-qPCR analysis of cell cultures and formalin-fixed paraffin-embedded tissues from samples corresponding to those used in cell culture. Lapatinib was able to inhibit cell proliferation in all cell cultures, but it was not able to inhibit migration in all cell cultures. The higher the expression of HER2 in a culture, the more sensitive the culture was to treatment. This relationship may be an indication that the expression of HER2 may be a predictive factor and opens a new perspective for the treatment of primary and metastatic mammary gland cancer.
Keywords: Cancer; Comparative oncology; Dog; Molecular targets